Borderless Lizards: Unveiling Overlooked Records and the Expanding Invasion of Anolis sagrei in Ecuador - Víctor Romero; Edison Maxi; Karen Cando; Marlon Vega; Johe Sozoranga; Luis Rodrigo Saa (Diversity)
We evaluated the global distribution of Anolis sagrei based on bibliographic records, GBIF, and iNaturalist data. Native to Cuba and the Bahamas, this lizard has spread across mainland America, particularly in the Caribbean, Central America, and parts of the U.S. It has also been introduced in Asia, and according to iNaturalist observations, it has been recorded in Israel, Canada, and northern South America. This species is especially abundant in the Caribbean and southeastern U.S., with high concentrations of records indicating a significant range expansion. In Ecuador, A. sagrei has been recorded along the coast and in the Amazon, with occurrences in Esmeraldas, Manabí, Guayas, Francisco de Orellana, and for the first time in Zamora Chinchipe (southern Amazon), specifically in El Pangui. The capture of 10 individuals confirmed their morphology, showing similarities with populations from Honduras and Cuba but differences in scalation and body size. In Ecuador, the fourth toe lamellae range from 29 to 33, consistent with those populations, while dorsal and ventral scales show variation (dorsal: 11–22, ventral: 10–25). Climate change favors its spread by enabling the colonization of new habitats. As an invasive species, it threatens local biodiversity, highlighting the need for monitoring and control in Amazonian Ecuador. An expanded abstract in Spanish is available, intended for local decision-makers.